STUDI KAITAN PARAMETER PENGEREMAN DENGAN BEBAN DINAMIS PADA KENDARAAN - Mustofa, Mustofa; Naharuddin, Naharuddin; Basri, Basri (Jurnal MEKANIKAL, 2010)
This research aims to study influence of parameters of brakes components and dynamic weight on vehicle. Car of Suzuki Katana is taken as sample of a braking study. Data was procured in the mechanical engineering laboratory of Tadulako University and in the Duty Communication of District of Kayumalue in North Palu. Result of calculation indicates that oil pressure put on the brakes pw (kg/cm2), tread force of a brake pedal Q (kg) and dynamic weight of vehicle (kg) both front wheels and rear wheels weights are parameters which are significant in studying the brakes system.